Aborted myocardial infarction in patients undergoing primary percutaneous coronary intervention - Pyda, Małgorzata; Grajek, Stefan; Oleśkowska-Florek, Weronika; Lesiak, Maciej; Siniawski, Andrzej; Gwizdała, Adrian; Grygier, Marek; Araszkiewicz, Aleksander (Journal of Medical Science, 2015)
Introduction. The outcome of patients with ST-elevation myocardial infarction (STEMI) strongly depends on a successful reperfusion. In some patients receiving an effective treatment myocardial infarction can be aborted.Aim. The aim of the study was to estimate the incidence, clinical outcome, prognosis and inflammatory response in patients with aborted MI.Material and methods. 119 consecutive patients with STEMI treated with a primary percutaneous coronary intervention (pPCI) were enrolled in the study. Aborted MI was diagnosed when the maximal increase in cardiac enzymes (CK-MB) was up to twice the upper limit of normal (CK-MB ? 50 U/I) and at least 50% reduction of ST-segment deviation was observed within 90 min of pPCI.Results. Aborted MI was diagnosed in 16 subjects (13.4%). Patients with the aborted MI had lower serum troponin I levels (p